2020
DOI: 10.3390/ijerph17207572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Unexpected Findings of Post-Mortem Computed Tomography in Hospitalized Patients: An Observational Study

Abstract: Background and objective: The current literature describing the use of minimally invasive autopsy in clinical care is mainly focused on the cause of death. However, the identification of unexpected findings is equally important for the evaluation and improvement of daily clinical care. The purpose of this study was to analyze unexpected post-mortem computed tomography (PMCT) findings of hospitalized patients and assess their clinical relevance. Materials and methods: This observational study included patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…For example, Leth et al studied 67 traffic fatality victims and found that PMCT was superior for identifying skeletal injuries, while autopsy diagnosed more soft tissue injuries [28]. Mentink et al found that in‐hospital deaths studied by both PMCT and autopsy ( n = 57), unexpected findings were observed in 32% of the cases [29]. Further, 25% of the unexpected findings were reported by PMCT but not reported by autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Leth et al studied 67 traffic fatality victims and found that PMCT was superior for identifying skeletal injuries, while autopsy diagnosed more soft tissue injuries [28]. Mentink et al found that in‐hospital deaths studied by both PMCT and autopsy ( n = 57), unexpected findings were observed in 32% of the cases [29]. Further, 25% of the unexpected findings were reported by PMCT but not reported by autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have proposed the use of PMCT to determine the cause of death [1][2][3][4][5][6][7][8][9][10]. The PMCT is considered the most feasible imaging modality because it is widely available.…”
Section: Case Historymentioning
confidence: 99%